Economic Dispatch Analysis of Hybrid Power Plant System in Islands Area Based on Linear Programming Method - Rusdianto Rusdianto; Eddy Setyo Koenhardono; Juniarko Prananda (International Journal of Marine Engineering Innovation and Research, 2020)
The increase in electricity demand in Selatpanjang, Meranti Island Regency, Riau continues to occur. However, the availability of diesel fuel types is increasingly scarce and the price is increasingly expensive. Therefore, another generator is needed, namely a relatively cheap coal-fired power plant and the availability of coal reserves in the Sumatran region. One of the problems in the economic operation of a generating system is economics dispatch, which is how to obtain minimum operating costs while meeting existing and reliable limits. For this reason, an economic dispatch analysis is needed for the optimal generating system by using the linear programming method. This economic dispatch analysis uses operational cost as a parameter and is done by using software assistance in the form of Matlab. Based on the results of loading with the same variation, the power generation based on economic dispatch calculations has an average load factor smaller than the average load factor based on unit commitment improvement calculations. Thus, the generation with economic dispatch has a higher specific fuel consumption (g/KWH) than the unit commitment improvement so that the fuel consumption price is issued higher.